A Paradigmatic Shift since the Velvet Revolution? State-of-the-art Research and new Historiographical Perspectives on the Pontifical Seminary of Olomouc (1579-1741) - TRENTA, Andrea (Studia Universitatis Babeș-Bolyai Historia, 2025)
Since the nineteenth century, the Olomouc Pontifical Seminary has been the object of numerous studies. Nevertheless, these research efforts rarely attempted to assess the overall impact of the seminary in the Margrave of Moravia and the territories under its supervision. To date, a comprehensive analysis of its development, from its inception until its suppression, is still missing. The grounds for the historiographical neglect towards this institution, which constituted a core element of the Jesuit mission in Olomouc, can be found in the cultural, socio-economic, linguistic, and political barriers that affected the historians dealing with this topic before the Velvet Revolution (1989), the re-establishment of the Czech Historical Institute in Rome (1994), and the entrance of the Czech Republic in the European Union (2004). The aim of this article, therefore, is to provide the readership with a panoramic review of the state-of-the-art research on the Olomouc Pontifical Seminary until 1992 and to outline the new historiographical perspectives opened with the demise of the communist Czechoslovakian regime. Rezumat: Încă din secolul al XIX-lea, Seminarul Pontifical din Olomouc a făcut obiectul a numeroase studii. Cu toate acestea, eforturile de cercetare au încercat rareori să evalueze impactul global al seminarului în Margravatul Moraviei și în teritoriile aflate sub supravegherea sa. Până în prezent, lipsește încă o analiză cuprinzătoare a evoluției sale, de la înființare până la desființare. Motivele neglijării istorice a acestei instituții, care a constituit un element central al misiunii iezuite din Olomouc, pot fi găsite în barierele culturale, socio-economice, lingvistice și politice care au afectat istoricii care s-au ocupat de acest subiect înainte de Revoluția de Catifea (1989), de reînființarea Institutului Istoric Ceh din Roma (1994) și de aderarea Republicii Cehe la Uniunea Europeană (2004). Scopul acestui articol este, așadar, de a oferi cititorilor o imagine de ansamblu asupra cercetărilor de ultimă oră privind Seminarul Pontifical din Olomouc până în 1992 și de a schița noile perspective istorice deschise odată cu căderea regimului comunist cehoslovac. Cuvinte cheie: Seminar pontifical; Olomouc; iezuiți; Revoluția de Catifea; Evul Mediu.